Islamic Human Development Index as a Development Indicator: An Empirical Study in Indonesia - KMT Lasmiatun; Muhammad Duku (LPPM Universitas Terbuka, 2025)
The Human Development Index (HDI) measures human development in the material dimension. This concept has not been able to become a measure of universal human development. The Islamic Human Development Index (I-HDI) measures human development through material and non-material aspects. Specifically, this concept can be a measurement of development in Muslim countries like Indonesia, namely as an effort to increase economic development. The purpose of this study is to determine the effect of economic growth, fiscal policy, and zakat on HDI and I-HDI with the maqāṣid al-sharī'ah approach. The research method uses a quantitative approach with dynamic panel regression two-step Generalized Method of Moments (GMM). The results of the statistical test analysis show that three of the independent variables have a positive and significant effect on HDI and I-HDI, namely economic growth and government expenditure fiscal policy in the health and education sectors. Meanwhile, the zakat variable only has a positive and significant effect on I-HDI and has a non-significant effect on HDI. This condition occurs because the management of zakat is not carried out optimally by zakat institutions, and there are no strict regulations from the government in encouraging an increase in the collection of zakat funds in Muslim communities in Indonesia.